PENGARUH WAKTU PEMBERIAN BOKASI GULMA DAN PEMANGKASAN DAUN TERHADAP PRODUKSI TANAMAN SORGUM (Sorghum bicolor L. Moench) - Zulkifli Zulkifli; Putri Lukmana Sari (DINAMIKA PERTANIAN, 2016)
This study aimed to find out the effect of bokasi gulma application time and leaf trimming on the production of Sorghum. This research was carried out during period from Desember 2015 to april 2016. The Research conducted in the Public Land on Jalan Penerbangan RT/05 RW/08 Kelurahan Simpang Tiga, Bukit Raya District, Pekanbaru City. The experiment was laid out in a completely randomized design in a 4 x 4 factoria. The First factor was time of bokasi gulma application, consisting og W1. (2 weeks before planting), W2. (planting time), W3. (2 weeks after planting), and W4. (4 weeks after planting). The second factor was the leaf trimming, consisting of T1 (without trimming), T2 (pruning age of 25 days after planting), T3 (trimmed age of 50 days after planting), T4. (trimmed age of 75 days after planting). The parameters observed were the length of panicle per panicle (cm), panicle dry weight per panicle/ plant (g) with water contain by 12%, weight of 1000 seeds per plant (g) and production (water contain by 12%) of dry sorghum per hectare (kg). The best treatment was W2T4 (time of giving bokasi gulma at planting and trimming the leaves when the plants of 75 days after planting) with the results; length of panicle per panicle (19.48 cm), panicle dry weight per panicle/plant of 112 grams KA 12%, weight of 1000 seeds per plant (38.07 grams), and production (KA 12%) of dried sorghum per hectare (6473.52 kg).